2009
DOI: 10.1186/1742-4690-6-s2-o14
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: A U5 repressor of reverse transcription is required for optimal HIV-1 infectivity and replication

Abstract: Here we provide strong evidence that a highly conserved stem loop structure in the U5 region of the HIV-1 RNA leader harbours a repressor of reverse transcription (RRT). We showed that two sequences in U5, at +143-145 and +151-153, are essential for RRT function. Mutation of either site strongly and unexpectedly increased endogenous reverse transcription, and cell infection assays showed that both mutations dramatically increased negative strand strong stop DNA synthesis. Early, late, 1-LTR and 2-LTR reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent work from the group of D. Harrich has shown that cellular factors stimulate reverse transcription in the target cells [ 143 ] ( Figure 6 ). Unexpectedly, recent data from the same group showed that the early steps of reverse transcription are negatively regulated in the target cells and that suppression of this negative control is detrimental to HIV-1 replication ( Figure 6 ) [ 144 ]. Thus, there is increasing evidence that initiation of reverse transcription is temporally regulated, both in the producer and in the target cells.…”
Section: Spatio-temporal Regulation Of Reverse Transcriptionmentioning
confidence: 99%
“…Recent work from the group of D. Harrich has shown that cellular factors stimulate reverse transcription in the target cells [ 143 ] ( Figure 6 ). Unexpectedly, recent data from the same group showed that the early steps of reverse transcription are negatively regulated in the target cells and that suppression of this negative control is detrimental to HIV-1 replication ( Figure 6 ) [ 144 ]. Thus, there is increasing evidence that initiation of reverse transcription is temporally regulated, both in the producer and in the target cells.…”
Section: Spatio-temporal Regulation Of Reverse Transcriptionmentioning
confidence: 99%